La crisis de la negociación colectiva y la discreta extinción del sindicato mayoritario en el Perú - Salvador Florian, Renzo Vito (2024)
Democratic opening scenarios provide favorable conditions for the development of workers’ organizations. However, these circumstances did not translate into sustained growth or recovery of pre-dictatorship indicators in Peru. The Peruvian literature tends to attribute it to the hyperdecentralization produced by the 1992 labor reform. This paper revisits this thesis to complement it and argues that the lack of adequate anti-union protection explains the lack of power of the organizations, particularly the consistent decline in collective bargaining coverage since 2006. For this purpose, we review the model and structure of collective bargaining from 1970 onwards, and the institutional framework in which unions operate. The research shows that the scope of collective bargaining agreements— during the first decade of the twenty-first century—exceeded union membership, indicating a significant number of majority unions within their unit. However, this ratio began to decline constantly from 2006 onwards, and with it started the quiet extinction of these organizations. According to the argument, this change is explained by the management practice of unilaterally extending the benefits of a collective bargaining agreement, given the effect of parasitic behaviour (free rider) on membership.